Acoustical Studies& Molecular Interactions of Antiepileptic Drug Levitiracetam in DMSO-Water Mixtures at Different Temperatures - Kumar, Kaushlendra; Sinha, Chandani (Asian Journal of Pharmaceutical Research and Development, 2021)
The densities and speeds of sound have been measured of ternary mixtures of Levitiracetam drug in aqueous dimethyl sulfoxide (DMSO) mixtures at 25% interval of the solvent at 303K,308 K,313 K and frequency 2MHz .The experimental data has been used to determine acoustic parameters like intermolecular free length (Lf),Specific acoustic impedence (z) etc.The changes in these properties with composition and temperature are used to interpret the nature of solute-solvent, solute-solute interactions in the system.